Characterization of new bone formation in gout: a quantitative site-by-site analysis using plain radiography and computed tomography - Dalbeth, Nicola (BioMed Central, 2012)
INTRODUCTION: Radiographic descriptions of gout have noted the tendency to hypertrophic bone changes. The aim of this study was to characterize the features of new bone formation (NBF) in gout, and to determine the relationship between NBF and other radiographic features of disease, particularly erosion and tophus. METHODS: Paired plain radiographs (XR) and computed tomography (CT) scans of 798 individual hand and wrist joints from 20 patients with gout were analyzed. Following a structured review of a separate set of images, films were scored for the presence of the following features of NBF: spur, osteophyte, periosteal NBF, ankylosis and sclerosis. The relationship between NBF and other radiographic features was analyzed. RESULTS: The most frequent forms of NBF were bone sclerosis and osteophyte. Spur and periosteal NBF were less common, and ankylosis was rare. On both XR and CT, joints with bone erosion were more likely to have NBF; for CT, if erosion was present, the odds ratios (OR) was 45.1 for spur, 3.3 for osteophyte, 16.6 for periosteal NBF, 26.6 for ankylosis and 32.3 for sclerosis, P for all < 0.01. Similarly, on CT, joints with intraosseous tophus were more likely to have NBF; if tophus was present, the OR was 48.4 for spur, 3.3 for osteophyte, 14.5 for periosteal NBF, 35.1 for ankylosis and 39.1 for sclerosis; P for all < 0.001. CONCLUSIONS: This detailed quantitative analysis has demonstrated that NBF occurs more frequently in joints affected by other features of gout. This work suggests a connection between bone loss, tophus, and formation of new bone during the process of joint remodelling in gout.